A high-yielding evaporation-based process for organic transistors based on the semiconductor DNTT - Abbas, GA; Ding, Z; Assender, HE; Morrison, JJ; Yeates, SG; Patchett, ER; Taylor, DM (Elsevier, 2014)
We report on the performance of organic thin film transistors manufactured in an all-evaporated vacuum roll-to-roll process. We show that dinaphtho [2,3-b:2′,3′-f] thieno[3,2-b]thiophene (DNTT) is a suitable semiconductor material for deposition onto a flash evaporated polymer insulator layer to make bottom-gate top-contact transistors. Significantly, in batches of 90 transistors, the process approached a 100% yield of high mobility transistors with high on/off ratios and low gate-leakage. By contrast, a solution-deposited insulator layer led to significant gate leakage in a high proportion of transistors leading to poor yield. The performance of DNTT devices is shown to be superior to that of previously reported pentacene devices. Transistor performance is further enhanced by inclusion of a low-polarity surface modification, such as polystyrene, to the acrylate. The devices show good environmental stability but we demonstrate also that they can be in-line encapsulated with an acrylate and a SiOx overlayer without damaging the underlying transistor. Finally, a first demonstration is made of organic vapour jet printing of the DNTT to manufacture transistors with a high semiconductor deposition rate.